Dari upper room ke open heart: Evolusi kepemimpinan Pentakostal-Karismatik kontemporer - Kusni, Markus; Runtuwene, Daniel (KURIOS, 2024)
This article explores the paradox of the early church that simultaneously displays resilient and fragile characteristics in its development. Through the lens of contemporary Pentecostal theology, this study examines how the early Christian community persisted and flourished amidst external challenges such as persecution and internal pressures exemplified by identity conflicts. The analysis demonstrates that the early church's resilience was rooted precisely in its acknowledgment of fragility. This ecclesiological model offers valuable insights for the contemporary church in confronting an increasingly complex world. This article proposes that Pentecostal theology can provide a fresh interpretive framework for understanding the dynamics of strength-in-weakness that characterizes the apostolic church by integrating pneumatological readings of the book of Acts and the Pauline epistles.   Abstrak Artikel ini mengeksplorasi transformasi paradigma kepemimpinan dalam tradisi Pentakostal modern, dengan fokus pada pergeseran dari model kepemimpinan karismatik-hierarkis menuju pendekatan hospitalitas yang lebih inklusif. Melalui analisis teologis dan sosiologis, penelitian ini mengidentifikasi bagaimana kepemimpinan Pentakostal kontemporer menggabungkan elemen karismatik tradisional dengan nilai-nilai hospitalitas yang menekankan keterbukaan, penerimaan, dan pemberdayaan komunitas. Studi ini menggunakan pendekatan kualitatif dengan analisis literatur untuk memetakan evolusi kepemimpinan ini dalam konteks global dan Indonesia.